Selected Management Factors of Diversifying the MSMEs Development Potential in the EU and LATAM Economies - Wilson GRUESO ORJUELA; Marek DUDEK (Communications of International Proceedings, 2021)
Micro, small and medium-sized enterprises (MSMEs) constitute a strategic business segment for the growth of every economy, including the EU and LATAM. However, despite their economic importance, SMEs and micro-enterprises in particular, are still the business segment most vulnerable to imperfections and asymmetries in the markets, and also to the high degree of improvisation of entrepreneurs. Evidence of this is the high percentage of business initiatives that fail before reaching the first five years of life. Hence, understanding the nature and dynamics of MSMEs is a key task to develop adequate public policies to promote the creation and consolidation of these types of companies, but also to generate significant learning in entrepreneurs, improving their chances of success. The empirical analysis exposes that the main causes of sluggish economic growth in LATAM region are weak governance and weak institutional framework, also that weak governance has unfavourable impact on macroeconomic performance of LATAM, indicating that good governance is critical for enviable level of economic growth and development (Azam, 2021). The article aims to compare the conditions of MSMEs functioning in economies EU and LATAM and on this basis, presenting business recommendations for enterprises in the LATAM area.
Keywords: MSMEs (Micro; Small; Medium – sized enterprises); Insertion; Business Networks.